2017
DOI: 10.1371/journal.pone.0184377
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a training program for police officers who come into contact with people with mental health problems: A pragmatic randomised controlled trial

Abstract: IntroductionPolice officers frequently come into contact with individuals with mental health problems. Specialist training in this area for police officers may improve how they respond to individuals with mental health problems; however, evidence to support this is sparse. This study evaluated the effectiveness of one bespoke mental health training package for frontline police officers relative to routine training.DesignPragmatic, two-armed cluster randomised controlled trial in one police force in England. Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…Another possible solution is ‘Street Triage’ (Horspool et al, )—a collaborative model of care that has been piloted in various police forces in England, which involves mental health nurses accompanying police officers to mental health‐based incidents (Scantlebury et. al, ). However, more research into the effectiveness of Street Triage is necessary, including resourcing and effect on inter‐agency working (Horspool et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another possible solution is ‘Street Triage’ (Horspool et al, )—a collaborative model of care that has been piloted in various police forces in England, which involves mental health nurses accompanying police officers to mental health‐based incidents (Scantlebury et. al, ). However, more research into the effectiveness of Street Triage is necessary, including resourcing and effect on inter‐agency working (Horspool et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Officers suggested that joint training would help services understand each other better, creating less potential for conflict. Another possible solution is 'Street Triage' (Horspool et al, 2016)-a collaborative model of care that has been piloted in various police forces in England, which involves mental health nurses accompanying police officers to mental health-based incidents (Scantlebury et. al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The included studies were of varying designs. One RCT evaluated a training programme for front-line officers, 47,48 although the remaining studies were largely descriptive, reporting little comparative data. Single studies used the following designs: a comparison of two different models of PRMHT interventions, 44 a largely single-group evaluation during a PRMHT intervention with some comparison data from a cost-benefit analysis, 46 an evaluation across multiple areas of PRMHT pilot interventions that reported comparative data only for some outcomes (e.g.…”
Section: Characteristics Of Primary Studiesmentioning
confidence: 99%